Actors and factors in the international transfer of dual training approaches: The coordination of vocational education and training in Mexico from a German perspective - Beke Vogelsang; Natascha Röhrer; Matthias Pilz; Martina Fuchs (International Journal of Training and Development, 2022)
The transfer of the German dual vocational education and training to other countries is much discussed. The reduction of youth unemployment, in particular, is considered as a central motive. Similarly, some promoting factors and challenges that influence the transfer of vocational education are already known. The focus of this study is on the reform of the Mexican vocational education system and the facilitating and inhibiting factors faced by the different actors from German-speaking countries involved. The study is based on 22 expert interviews that were analysed using qualitative content analysis. The results show that there are factors that have both a positive and a negative impact on transfer in Mexico.
Keywords: 650